Causes of Business Success or Failure of Start-Ups Company-A Case of Kathmandu Valley - Subedi, Roshani (Nepalese Journal of Finance, 2024)
This study examines the causes of business success or failure of start-ups in Kathmandu Valley. Business success is the dependent variable. The independent variables are suitable environment, self-motivation, family background, ICT, product and services, strategy, resource and finance. The primary source of data is used to assess the opinions of the respondents regarding the causes of success or failure of start-ups in Kathmandu Valley. The study is based on primary data with 122 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of factors associated with causes of business success or failure of start-ups companies in Kathmandu Valley.The result shows that suitable environment has a positive impact on business success. It indicates that suitable environment for starts up leads to business success for Nepalese start-ups companies. Likewise, self-motivation has a positive impact on business success. It indicates that higher self-motivation leads to business success. Similarly, family background has a positive impact on business success. It implies that strong family background of the business person leads to business success. Similarly, ICT has a positive impact on business success. It indicates that use of information communication technology in the organization leads towards business success. Similarly, product and services has a positive impact on business success. It indicates better the quality of product and services business offering, higher would be the chances of business success. In addition, strategy has a positive impact on business success. It indicates that the most effective strategy leads towards business success. Likewise, resource and finance has a positive impact on business success. It indicates that maintaining a good balance between resources and finance leads towards business success.